A Hybrid Approach To Solving The View Selection Problem In Data Warehouse - Alaoui, Mohammed El; Moutaouakil, Karim El; Ettaouil, Mohamed (International Journal of Computer Sciences and Engineering, 2018)
A data warehouse is a centralized repository of information from one or more data sources. The amount of big data that arrives in data warehouse typically comes from transactional systems and other relational databases. Often the data is stored in the form of materialized views in order to improve the performance of query execution in data warehouse. One of the most important techniques for improving query optimization performance is the selection of views to materialize. In this paper, the views selection problem is modelled as constraint satisfaction and optimization problem. The exact method standard may take a considerable amount of time in order to find an optimal solution. To address this limitation of the exact method, we proposed an approach based on consistency techniques and systematic search techniques to select an optimal set of views for materialization. This proposed approach improves the quality of execution time for selecting an optimal set of views to materialize.